Clarifying the mechanisms and resources that enable the reciprocal involvement of seldom heard groups in health and social care research: A collaborative rapid realist review process. (6th February 2019) - Ní Shé, Éidín; Morton, Sarah; Lambert, Veronica; Ní Cheallaigh, Cliona; Lacey, Vanessa; Dunn, Eleanor; Loughnane, Cliona; O'Connor, Joan; McCann, Amanda; Adshead, Maura; Kroll, Thilo
Abstract: Objective: Public and patient involvement is increasingly embedded as a core activity in research funding calls and best practice guidelines. However, there is recognition of the challenges that prevail to achieve genuine and equitable forms of engagement. Our objective was to identify the mechanisms and resources that enable the reciprocal involvement of seldom heard groups in health and social care research. Methods: A rapid realist review of the literature that included: (a) a systematic search of CINAHL, PsycINFO, PubMed and Open Grey (2007‐2017); (b) documents provided by expert panel members of relevant journals and grey literature. Six reference panels were undertaken with homeless, women's, transgender, disability and Traveller and Roma organizations to capture local insights. Data were extracted into a theory‐based grid linking context to behaviour change policy categories. Main results: From the review, 20 documents were identified and combined with the reference panel summaries. The expert panel reached consensus about 33 programme theories. These relate to environmental and social planning (7); service provision (6); guidelines (4); fiscal measures (6); communication and marketing (4); and regulation and legislation (6). Conclusions: While there is growing evidence of the merits of undertaking PPI, this rarely extends to the meaningful involvement of seldom heard groups. The 33 programme theories agreed by the expert panel point to a variety of mechanisms and resources that need to be considered. Many of the programme theories identified point to the need for a radical shift in current practice to enable the reciprocal involvement of seldom heard groups.